Band gap modification in doped MXene: Sc2CF2 - Balci, Erdem; Akkus, Unal Ozden; Berber, Savas (Royal Soc Chemistry, 2017)
We report the modification of the band gap in the Sc2CF2 MXene monolayer through C atom substitution by Si, Ge, Sn, F, S, N, B, and B + N. Our geometry optimizations, total energy and electronic structure calculations are performed in Density Functional Theory. We find that Si, Ge, Sn, B, and B + N doped Sc2CF2 monolayers remain semiconducting with band gap values ranging from 0.55 eV to 0.24 eV. Thus, it is possible to obtain several different band gap values. Semiconductor to metal transition is observed in F, S, and N doped monolayers as well as in C monovacancy. In the B doped system, spin polarization due to the half filling of a defect band is observed. Our total energy results indicate that the substitutional dopings of the MXene monolayer by F, N, S, and B + N are favorable, and energy penalties for Si, Ge, and Sn are not formidable. On the other hand, the substitution in the bulk Sc2AlC MAX phase, the precursor of the Sc2CF2 monolayer, is exothermic for all our substituents. C substitution in the Sc2CF2 MXene monolayer is a powerful and feasible tool to adjust the electronic properties.
Keywords: Magnetic-Properties; Transition; Monolayer